Bilateral Tension Pneumothorax Following Equipment Improvisation. - Zambricki, Christine; Schmidt, Carol; Vos, Karen (AANA Journal, 2014)
This case report describes an unexpected event that took place as a result of using improvised equipment. The patient, a 16-year-old female undergoing complex oral surgery, suffered bilateral pneumothorax following the improper use of an airway support device. During the immediate postoperative period with the patient still intubated, oxygen tubing was attached to a right angle elbow connector with the port closed and 10 L/minute oxygen flow was administered to the patient in a manner that did not allow the patient to exhale. Within seconds, pneumothorax was apparent as the patient's vital signs deteriorated, visible swelling was noted in the shoulders and neck, and there was an absence of breath sounds on auscultation. This case study has application beyond the immediate discussion of bilateral pneumothorax, serving as a caution about the unintended consequences of equipment improvisation. In addition to highlighting the hazards of providing patient care with a non-standard device, this study also provides a powerful example of the human factors that can contribute to medical errors in the healthcare setting.